Strategi Influencer dalam Upaya Meningkatkan Niat Beli di Social Commerce - Sari, Prasiani Purnama (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
Society has begun to question influencer reviews in social commerce, despite influencers remaining essential in marketing. This research aims to gather effective strategies for influencers in social commerce to enhance purchase intention. The study utilizes the Systematic Literature Review method and identifies 15 documents meeting the criteria following a limitation process. The gathered strategies to support influencers and brand activities include enhancing parasocial relationships, possessing distinct characteristics, increasing interactions, utilizing attributes, garnering high numbers of 'likes' and 'comments,' avoiding hashtag usage, and informing about preannouncement discounts. The strategies found provide a comprehensive framework for influencers, brands, and researchers to navigate the dynamic landscape of social commerce, ensuring effective engagement, trust-building, and positive outcomes for all stakeholders involved. This systematic literature review can be revisited to ascertain if there have been changes or additions to influencer strategies in social commerce, given the rapid evolution of algorithms and trends, necessitating adjustments from influencers, brands, and relevant stakeholders.